2018
DOI: 10.1038/s41416-018-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of everolimus (RAD001) monotherapy as first-line treatment in advanced biliary tract cancer with biomarker exploration: the RADiChol Study

Abstract: In unselected patients, everolimus demonstrated clinical activity as first-line monotherapy in advanced BTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
1
35
1
Order By: Relevance
“…A phase I study reported that Everolimus achieved 50% disease-control-rate in a subgroup of 22 advanced CCA patients ( [104], Table 2). Subsequently a phase II study, in which patients with advanced CCA were enrolled, used Everolimus as a treatment option reporting an OS of 9.5 months [105]. At the same time in a phase II Italian study with Everolimus 39 patients with advanced and pre-treated CCA had progression-free survival (PFS) of 3.2 months, and OS of 7.7 months [106] while an Australian phase II study with Everolimus, conducted on patients with advanced CCA, showed objective response rate of 12 % and PFS of 6.0 months.…”
Section: Pi3k-akt-mtor Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I study reported that Everolimus achieved 50% disease-control-rate in a subgroup of 22 advanced CCA patients ( [104], Table 2). Subsequently a phase II study, in which patients with advanced CCA were enrolled, used Everolimus as a treatment option reporting an OS of 9.5 months [105]. At the same time in a phase II Italian study with Everolimus 39 patients with advanced and pre-treated CCA had progression-free survival (PFS) of 3.2 months, and OS of 7.7 months [106] while an Australian phase II study with Everolimus, conducted on patients with advanced CCA, showed objective response rate of 12 % and PFS of 6.0 months.…”
Section: Pi3k-akt-mtor Signaling Pathwaymentioning
confidence: 99%
“…At the same time in a phase II Italian study with Everolimus 39 patients with advanced and pre-treated CCA had progression-free survival (PFS) of 3.2 months, and OS of 7.7 months [106] while an Australian phase II study with Everolimus, conducted on patients with advanced CCA, showed objective response rate of 12 % and PFS of 6.0 months. Recently in 27 unselected patients, Everolimus displayed clinical activity as first-line monotherapy in advanced CCA with PFS of 5.5 months and OS of 9.5 months [105]. In another phase II study that aimed to evaluate the activity of Everolimus in 10 patients with PIK3CA amplification/mutation or PTEN loss refractory solid cancer, only one patient with CCA with PTEN loss experienced disease control ( [107], Table 2).…”
Section: Pi3k-akt-mtor Signaling Pathwaymentioning
confidence: 99%
“…6,16 In line with this, there are already clinical trials using Everolimus for cancer therapies. 17 In the present work, we however, report that the potent anti- reported to activate the Rac pathway, which culminates in morphological and migratory responses of the endothelium. 10,18,19 These findings are somehow reminiscent of our recent data in brain tumors highlighting the propagation of adhesion and migration cues via extracellular vesicles.…”
Section: Discussionmentioning
confidence: 55%
“…RADIANT-4 (NCT01524783) [62,63] Tuberous sclerosis complex NCT00457808 [47] ; NCT00490789 [48,49] ; NCT00411619 [50] ; NCT00126672 [51] ; EXIST-1 (NCT00789828) [52] ; [53] Potential clinical benefit Biliary tract cancer RADiChol study (NCT00973713) [64] ; EUDRACT 2008-007152-94 [125] Thyroid cancer (in patients refractory to other agents) NCT01263951 [126] ; NCT00936858 [127] No clinical benefit seen Gastric cancer GRANITE-1, NCT00879333 [ mTORC1 activity also cross-talks with, as well as negatively regulates, the catabolic process of autophagy. While rapamycin treatment is often less effective at re-activating autophagy in mammalian cells than in yeast [80] , mTORC1 inhibition could permit some reactivation of autophagy in cancer cells, thus allowing them to recycle macromolecules more effectively, maintain homeostasis and survive.…”
Section: Cancer/disease Type Study and Reference Food And Drug Adminimentioning
confidence: 99%